Atomic gas fractions in active galactic nucleus host galaxies. Issue 4 (22nd November 2018) - Ellison, Sara L; Brown, Toby; Catinella, Barbara; Cortese, Luca
ABSTRACT: The feedback from an active galactic nucleus (AGN) is frequently invoked as a mechanism through which gas can be heated or removed from a galaxy. However, gas fraction measurements in AGN hosts have yielded mixed support for this scenario. Here, we revisit the assessment of f gas (= MH I /M⋆ ) in z < 0.05 AGN hosts in the Sloan Digital Sky Survey (SDSS) using two complementary techniques. First, we investigate f gas for 75 AGN host galaxies in the extended GALEX Arecibo SDSS Survey (xGASS), whose atomic gas fractions are complete to a few per cent. Second, we construct H i spectral stacks of 1562 AGN from the Arecibo Legacy Fast ALFA (ALFALFA) survey, which enables us to extend the AGN sample to lower stellar masses. Both techniques find that, at fixed M⋆, AGN hosts with log (M⋆ /M⊙ ) ≳ 10.2 are H i rich by a factor of ∼2. However, this gas fraction excess disappears when the control sample is additionally matched in star formation rate (SFR), indicating that these AGN hosts are actually H i normal. At lower stellar mass, the stacking analysis reveals that AGN hosts are H i poor at fixed stellar mass. In the lowest M⋆ regime probed by our sample, 9 < log (M⋆ /M⊙ ) < 9.6, the H i deficit in AGN hosts is a factor of ∼4, and remains at a factor of ∼2 even when the control sample is additionally matched in SFR. Our results help reconcile previously conflicting results, by showing that matching control samples by more than just stellar mass is critical for a rigorous comparison.